Effect of Structure and Phase Composition on Thermocyclic Stability of Thermo-Barrier Coatings Zr-O Deposited by Microplasma Method on a Copper Substrate - Dorofeeva T. I.; Gubaydulina T. A. Tatiana Anatolievna; Gritsenko B. P. Boris Petrovich; Sergeev V. P. Viktor Petrovich (2018, 2018)
Title screen